Postharvest characterization of tacaco (Sechium tacaco (Pittier)) fruits in Cartago, Costa Rica. - Cerdas-Araya, María del Milagro (2016)
The aim of this work was to make a postharvest characterization of tacaco fruits in different chronological ages. During July and August of 2014, and January and February of 2015 newly set fruits, with or without thorns, from Cartago, Costa Rica were evaluated. Seven days after setting for the tacaco fruits without thorns (TWOT) and eight days after setting for the tacaco fruits with thorns (TWT), weight, length and width of the fruit, presence and hardening of the thorns, and emergence of ber were evaluated. The length and thickness of the seed, the firmness, and external color of the peel, were evaluated after day fourteen. In both material, weight, length and width of the fruit stabilized after day twenty-one, moment in which ber and thorns appeared, and a significant increase in firmness was registered, which by day thirty reached values of 80 N to 100 N in tacaco thorns and up to 129 N in thorn less fruits. The color of the peel went from a yellowish green in the unripen stage to a greyish green in the ripened stage by day thirty, close to the moment of the fruit’s separation. Before day twenty-one TWOT or TWT, can be used as unripen fruit, because there isn’t any presence of ber; and the peel and thorns have not yet hardened.